Enhancing cybersecurity: A comprehensive approach to addressing the growing threat of cybercrime - Silva, Jammylly Fonseca (Revista Sistemática, 2024)
The rise of technology and internet usage has revolutionized interactions and business practices but has also significantly increased the prevalence of cybercrime. Cybercrimes, including data theft, ransomware, attacks on critical systems, and botnet-driven attacks, have grown more sophisticated and damaging. Recent research by Mphatheni and Maluleke (2022), Cascavilla, Tamburri, and Heuvel (2021), Shah and Chudasama (2021), Dupont and Whelan (2021), Djenna et al. (2023), and Back and LaPrade (2020) offers a detailed analysis of contemporary cybersecurity challenges and emerging solutions. These studies emphasize the need for a comprehensive approach to combating cybercrime. Mphatheni and Maluleke (2022) highlight the absence of a universal definition for cybercrime, which undermines prevention efforts and overlooks the global economic impact, particularly in Africa. Cascavilla, Tamburri, and Heuvel (2021) stress the importance of advanced machine learning techniques and threat intelligence for detecting cybercrimes across various web layers, advocating for improved risk assessment and anonymity measures. Shah and Chudasama (2021) propose a new cybercrime taxonomy to address gaps in current legislation, especially in regions like India where crimes often stem from data issues or malicious intent. Dupont and Whelan (2021) call for greater integration between cybercriminology and cybersecurity, promoting a continuous approach that fosters better collaboration between security and crime control domains. Djenna et al. (2023) introduce an advanced deep learning method for early botnet attack detection, enhancing forensic investigations and threat response. Back and LaPrade (2020) emphasize updating cybersecurity practices in academic institutions using a Situational Crime Prevention (SCP) framework to improve digital security. Overall, a proactive and coordinated strategy, incorporating new technologies, enhanced practices, and updated legislation, is essential for effective cybercrime prevention and response. Collaboration among governments, the private sector, and academia is crucial for developing robust defenses against escalating cyber threats.